The Glucocorticoid PYED-1 Disrupts Mature Biofilms of Candida spp. and Inhibits Hyphal Development in Candida albicans - Anna Esposito; Antonella Migliaccio; Vita Dora Iula; Raffaele Zarrilli; Annalisa Guaragna; Eliana De Gregorio (MDPI AG, 2021)
Invasive Candida infections have become a global public health problem due to the increase of Candida species resistant against antifungal therapeutics. The glucocorticoid PYED-1 (pregnadiene-11-hydroxy-16α,17α-epoxy-3,20-dione-1) has antimicrobial activity against various bacterial taxa. Consequently, it might be considered for the treatment of Candida infections. The antifungal activity of PYED-1 was evaluated against several fungal strains that were representative of the five species that causes the majority of Candida infections-namely, Candida albicans, Candida glabrata, Candida tropicalis, Candida parapsilosis and Candida krusei. PYED-1 exhibited a weak antifungal activity and a fungistatic effect on all five Candida species. On the other hand, PYED-1 exhibited a good anti-biofilm activity, and was able to eradicate the preformed biofilms of all Candida species analyzed. Moreover, PYED-1 inhibited germ tube and hyphae formation of C. albicans and reduced adhesion of C. albicans to abiotic surfaces by up to 30%.